Lentiviral Vector Design for Optimal T Cell Receptor Gene Expression in the Transduction of Peripheral Blood Lymphocytes and Tumor-Infiltrating Lymphocytes - Jones, Stephanie (Mary Ann Liebert, Inc., 2009)
Lentiviral vectors containing promoters of distinct origins, that is, strong viral promoters (cytomegalovirus [CMV] and murine stem cell virus [MSCV]), a cellular promoter (phosphoglycerate kinase [PGK]), and two composite promoters (CAG [a composite promoter sequence comprised of the CMV enhancer and portions of the chicken β-actin promoter and the rabbit β-globin gene] and SV40/CD43), were used to evaluate green fluorescent protein (GFP) reporter gene expression in human primary peripheral blood lymphocytes (PBLs) and tumor-infiltrating lymphocytes (TILs). In PBLs, vectors containing the MSCV promoter were found to be optimal for expression in both minimally stimulated and highly activated lymphocytes. The stability of gene expression was monitored for up to 7 weeks in culture and the MSCV promoter-containing vector was found to be comparable to the cellular PGK promoter-containing vector. The MSCV promoter-containing lentiviral vector was also the most active in transduced TILs and these cells retained biological activity as measured by antimelanoma antigen reactivity. Using the knowledge gained in comparing individual promoters, a series of two-gene-containing lentiviral vectors was constructed in an attempt to produce the α and β chains of antitumor antigen T cell receptors (TCRs). Dual-promoter or internal ribosome entry site (IRES)-containing vector designs were evaluated and found to be unable to produce both chains of the TCR in amounts that led to significant biological activity. In contrast, if the α and β chains were linked by a 2A ribosomal skip peptide, both proper TCR chain pairing and biologically activity were observed. This paper emphasizes the need to optimize both promoter function and protein synthesis in constructs that require stoichiometric production of multiple protein subunits.